Antioxidant and Choline Esterase Inhibitory Activity of Phenolic Rich Extracts from Bombax ceiba L. Flowers - Sinha, Sonal; Kumar, Brijesh; Singh, Dhananjay Kumar; Luqman, Suaib; Singh, Manish; Singh, Ashutosh (Free Radicals and Antioxidants)
Background: Cognition impairment is the most recurrent form of dementia in aged people indicated by permanent neuronal loss and atypical behaviour. Disparities in cholinergic pathway have been reported as major cause of cognition impairment, where deficiency of acetylcholine occurs due to hydrolysis of acetylcholine by cholinesterases. Bombax ceiba (Bombacaceae) commonly known as silk cotton tree is an imperative plant of tropical and subtropical region which have been mentioned in the traditional systems of medicine. Objectives: We have investigated the cholinesterase and antioxidant activity of B. ceiba extracts. Besides these activity evaluations, preliminary phytochemical testing and quantification of total phenolic and flavonoids have also been performed. Method: Extracts from B. ceiba flowers in hexane and ethanol were prepared by cold maceration method. In vitro cholinesterase activity was estimated with the help of Ellman’s reagent, antioxidant potential of extracts was determined by well known method such as DPPH, FRAP, reducing power and total antioxidant power assay. Total phenolics and flavonoids were quantified by colorimetric method. Results: Finding of present study indicated that B. ceiba extracts are rich in polyphenolic contents (19.10 ± 0.74 QcE and 28.01 ± 1.28 GaE). Results of antioxidative potential evaluation suggested that these extracts have high free radical scavenging potential (65.49 ± 2.49%) and are also able to reduce iron like radicals (93.78 FSE). Beside antioxidant potential B. ceiba extracts also inhibited the cholinesterase effectively (IC50 31.22 ± 1.42 μg/ml). Conclusion: Current investigation on B. ceiba flowers indicated that phenolic rich extracts could be used in development of effective plant-based cholinesterase inhibitors.
Keywords: Bombax ceiba; Phenolics; Choline esterase; Antioxidant; Cognition